Remarkable Diagnostic Magnetic Resonance Imaging Findings in Sellar Xanthogranuloma: Report of Three First Cases in Latin America - Céspedes, Mario Tapia; Vargas, Jaime Pinto; Yañez, Fernando Andrade; León, Loreto Spencer; Arancibia, Pablo Álvarez; Putz, Thomas Schmidt (Journal of Neurological Surgery Reports, 2017)
The sellar xanthogranuloma is a rare lesion of the sellar–parasellar region difficult to differentiate from other tumors such as craniopharyngiomas or Rathke's cleft cyst in the preoperative evaluation. As they are recently recognized as a separate entity and the few number of reports in the literature, its etiology is unknown and its impact remains uncertain. This article will describe the first three cases reported in Latin America, identified in one of them an imaging feature that may be helpful to elucidate an imaging growth pattern. Current evidence will be described regarding to the clinicopathological features, imaging diagnosis, and etiology origin theories.
Keywords: xanthogranuloma; craniopharyngioma; sellar region; MRI